Web-based Q&A service for farmers in ACP countries - Knipschild, Henning; Oguya, Vivienne (Technical Centre for Agricultural and Rural Cooperation, 2005)
Henning Knipschild and Vivienne Oguya explain how CTA's web based question and answer service helps farmers to obtain expert advice.